PENJADWALAN BATCH PADA HYBRID FLOWSHOP DUA TAHAP UNTUK MEMINIMASI TOTAL ACTUAL FLOW TIME - Tengku Nurainun (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2011)
The hybrid flowshop (HFS) manufacturing system or multiprocessor flowshop is commonly applied to industries like cosmetics, pharmaceuticals, textile, food industry, and electronics, like IC packaging and PCB production. In these industries, production facilities are organized as the processing stages and at least one of the stages consist of two parallel machines. This research develop a batch scheduling model for a  two stage flowshop  and at least one of the stages consist of several heterogeneous machines that have ability to produce the same output but at least one of the machines has different setup time and/or processing time from another machine. The objective of the problem is to minimize total actual flow time that has considered due date in its formulation. The problems that have to be solved in this research are allocating parts to available resources, batching the allocated parts, and sequencing the resulting batches. These problem are solved simultaneously. Numerical experiences show that the proposed model works in solving a flowshop batch scheduling problem with two stages consisting of heterogeneous machines. The resulting solution has been proven optimal.  Keywords: batch scheduling, hybrid flowshop, heterogeneous machines, total actual flow time